Feeding habits of the apron ray, Discopyge tschudii (Elasmobranchii: Narcinidae), from off Uruguay and northern Argentina - Spath, María Cecilia (2013)
The feeding habits of the apron ray, Discopyge tschudii, were investigated, off Uruguay and northern Argentina, and we tested the hypothesis that the diet changes with increasing body size, between sexes and seasons using a multiple-hypothesis modeling approach. D. tschudii preys mainly on polychaetes (88.77 %IRI) followed by siphons of the clam Amiantis purpurata (8.13 %IRI) and amphipods (3.08 %IRI). Ontogenetic, sexual and seasonal changes were found. Larger individuals of D. tschudii consumed buried polychaetes more often. The consumption of errant polychaetes was higher in males and in the cold season. Also, amphipods were preyed on more heavily by females and the number of siphons of A. purpurata consumed was higher in the cold season.